Rob Thelen email to Thomas Kent regarding field reports, June 4, 1999 - Thelen, Robet al (1999)
Printout of an email from Rob Thelen to Thomas Kent dated June 4, 1999. Thelen replies to Kent's questions about Red-necked Grebe and other sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed